Deposit Insurance and Digital Financial Inclusion - Izaguirre, Juan Carlos; Lyman, Timothy; McGuire, Claire; Grace, Dave (World Bank, Washington, DC, 2016)
Policy makers worldwide are increasingly appreciating the expanding role that digital financial services play in reaching financially excluded and underserved customers. Though models vary widely, all have at their heart a low-cost digital financial product such as e-money issued by a mobile network operator (MNO) or financial institution that permits customers to make payments, to transfer money, and to store value in small amounts. This value-storage functionality enables the offering of additional services such as digital credit and off-grid electricity on a pay as one go basis - services better tailored to the unpredictable cash flow of poor households and microenterprises.